Extracellular matrix derived from human urine-derived stem cells enhances the expansion, adhesion, spreading, and differentiation of human periodontal ligament stem cells - Xiong, Xue; Yang, Xiao; Dai, Hongwei; Feng, Gang; Zhang, Yuanyuan; Zhou, Jianping; Zhou, Wenwen (Stem cell research & therapy, 2019)
Human periodontal ligament stem cells (hPDLSCs) are one of the most promising types of seed cells in periodontal tissue regeneration. Suitable biomaterials are additional essential components that must cooperate with seed cells for in vivo expansion or in vitro implantation. Extracellular matrix (ECM) derived from mesenchymal stem cells (MSCs) was recently reported to be a promising substrate with which to culture MSCs that could be applied in biomaterial scaffolds or bioink. Human urine-derived stem cells (hUSCs) have several advantages; their collection is non-invasive and easy, and hUSCs are low in cost, potentially making them a suitable and efficient source of ECM. The purpose of this study was to characterize the biological properties of ECM derived from hUSCs (UECM) and evaluate the effects of UECM on hPDLSCs. hPDLSCs grown on ECM derived from hPDLSCs (PECM) and fibronectin-coated tissue culture plastic (TCP) served as control groups. Both hUSCs and hPDLSCs were seeded on TCP and stimulated to produce ECM. After 8 days of stimulation, the samples were decellularized, leaving only ECM. Then, hPDLSCs were seeded onto UECM-, PECM-, and fibronectin-coated TCP and untreated TCP. UECM consists of dense bundles of fibers which contain abundant fibronectin. Both UECM and PECM promoted hPDLSC proliferation, attachment, spreading, and differentiation. Between UECM and PECM, UECM enhanced proliferation, osteogenesis, and angiogenesis to a greater extent. Though fibronectin appeared to be the abundant component of UECM, its performance was inferior to that of UECM. Our study provides an original perspective on different cell-specific ECMs and suggests UECM as a suitable biomaterial in which to culture hPDLSCs as UECM enhances their biological functions.